Assessment of fungal and bacterial populations on selected vegetable crops using the vertical hydroponics system - Mustaffa, Mohd Alif Omar (2016)
The vertical hydroponics system is a method for plant cultivation that using the height of a hydroponics system. The role of microbes in plants growth is a very important. All plant surfaces have microbes on them, fungi and bacteria are among the microbes that successively colonize plants as they mature. Therefore, the objective of this study was to determine populations of fungi and bacteria on selected vegetable crops using vertical hydroponics system. The study was conducted to assess the high concentration on both populations of fungi and bacteria on Lemon Basil (Ocimum americanum), Chinese Kale (Brassica oleracea var. alboglabra), Hong Kong Choy Sum (Brassica chinensis var. parachinensis) and Lion Head Lettuce (Lactuca sativa). The experiment was conducted at the glasshouse in the urban agriculture unit at Faculty of Agriculture, Universiti Putra Malaysia. CFU/mL was be used in enumeration of fungi and bacteria populations using surface plating method and direct plating method from root and water sampling on selected vegetable crops within four week was assessed. Based on the results, the selected vegetable crops showed that there was significant different on fungi and bacteria populations. In fungi population, B. oleracea var. alboglabra and L. sativa has high concentration in root sampling and O. americanum also has high concentration in water sampling. For bacteria population, L. sativa has high concentration in the both of root and water sampling. The new finding in this study, the both populations of fungi and bacteria is more to give the beneficial microbes on selected vegetable crops and will be useful to plant growth in vertical hydroponics system. In conclusion, Aspergillus fumigatus, Aspergillus niger, Cladosporium herbarum, Curvularia lunata, Bacillus subtilis, Proteus vulgaris, Staphylococcus aureus and Streptococcus pyogenes were found from root and water sampling using morphological identification method.